From Data to Decisions: How Quality Drives Machine Learning Success - Ravikumar Mani Naidu Gunasekaran (Eastasouth Institute, 2024)
In the era of data-driven decision-making, machine learning (ML) has emerged as a critical tool for extracting insights and enabling intelligent automation across industries. However, the success of ML models is fundamentally dependent on the quality of the data used throughout the analytics pipeline. This article explores the relationship between data quality and machine learning performance, emphasizing how data integrity directly impacts model accuracy, reliability, and fairness. Key dimensions of data quality—including accuracy, completeness, consistency, and timeliness—are examined in the context of real-world ML applications. The article further discusses common data challenges such as missing values, noise, bias, and data drift, highlighting their implications on predictive outcomes. Additionally, it presents practical approaches to improving data quality through data preprocessing, validation, governance frameworks, and automated monitoring systems. By bridging the gap between raw data and actionable insights, this study underscores that high-quality data is not merely a prerequisite but a strategic enabler of successful machine learning initiatives. Organizations that prioritize data integrity can achieve more robust models, better decision-making, and sustain competitive advantage in an increasingly data-centric world.